SPECTROSCOPIC STUDIES OF FLUORESCENT COMPLEXES OF TYROSINE-8-HYDROXY QUINOLINE AND TYROSINE-8-HYDROXYQUINALDINE IN AQUEOUS PHASE (Biological Sciences - PJSIR, 2002)
A new method has been developed by preparing complexes involving condensation of tyrosi ne with  8-hydroxyqui noline (Oxine) and 8-hydroxyquinaldine (Quinaldine) respectively, producing  fluorescent  products  The  product s obtained  have been investigated for identification and q uantitative estimation using different spectroscopic techniques i ncl uding fluores cence acti vity of newly synthesized products. 8-hydroxyq uinaldine and 8-hydroxyquinoli ne  (Oxine)  condensed  with tyrosine separately produced water-sol uble fluorescent complexes. The complexes have been  investigated  for identification and quantitative estimation of amino acids. Identification of amino acids in nano mole or below than nano mole has become possible by present fluorometric activity of these complexes invol ving different excitation and emission wavelengths. The fluorometric activity of complexes has been observed to be 100 to I 000 times higher than assay method involving ninhydrin  and amino acid  analyzer.The method adopted in our laboratory is ra pid , versatile with good reproduci bility and provides excellent results for adoption by analytical , agricultural and biomedical laboratories to estimate amino acids and metals in composite matrix.